If the median nerve transposition is safe for treating the carpal canal syndrome - Malanchuk, Roman; Goloborod'ko, Sergey; Pokhvaliy, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The purpose of the work consists in the confirmation or refutation of the fact that, following its transposition, the median nerve really undergoes an undesirable overirritation in case of a mechanical load in the region after a surgical scar. In order to measure a pain threshold, a so-called F-Meter (a pain indicator, an algometer) from a set of the device for shock-wave therapy (Storz Medical Masterpuls® MP100) was used. The study on the operated and nonoperated hands in the same four points was performed in 12 patients, who underwent the median nerve transposition for treating their carpal canal syndrome. The results of the study confirmed that pain sensations on the operated and nonoperated hands developed actually with the same external mechanical effect on the region of the median nerve projection. The above fact served as a basis for concluding that the median nerve did not undergo any hyperirritation, and hence the operation itself was quite safe in this respect.